Contributions to the Analysis of the Conditions of Possibility for Biotechnological Innovation: The Response of the Argentine Scientific-Technological System to the Pandemic (Desarrollo Económico. Revista de Ciencias Sociales, 2023)
During the COVID-19 pandemic, several research and development (R&D) projects sought to provide a prompt response to novel problems. Thus, it constituted a unique scenario to observe in action the strategies deployed by the actors to produce innovative goods and services. This paper briefly reconstructs the history of some of these biotechnology-based R+D+i projects, with the aim of understanding the limits and potential of the national scientific-technological system. To do this, we start from a series of difficulties and virtues of working with cutting-edge biotechnology in Argentina, which we identified in a previous investigation on new gene editing techniques. Based on the testimonies of the participating scientists-researchers and other secondary sources, we will see how the (short) favorable conditions that exist in the country managed to articulate positively to overcome the obstacles and produce treatments and products to face the pandemic.
Keywords: Research and development; technological innovation; biotechnology; pandemic